Indonesia’s Prospect of the Halal Food Industry After COVID-19 Pandemic - Eka Fitriyanti; Vebtasvili (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2022)
This article discusses the prospects of the halal food industry in Indonesia after the COVID-19 pandemic. How with the real condition happened in society during this pandemic, especially for the halal food industry? And What are the opportunities and challenges of the halal food industry? This study observes that Indonesia has various opportunities to be maximized in developing the halal food industry after the COVID-19 pandemic. These opportunities can be an exploration of natural resources into halal food products, such as increasing export of Indonesia's halal food, developing e-commerce for halal food products, and globalizing the halal food events. Meanwhile, this study explains more about several challenges that need to be considered such as aspects of human resources, infrastructure, a production that has not created a model for the integrity to the halal industry from upstream to downstream, technology and information, and also the role of Islamic financial institutions as a distributor of capital.